Charming the generals: the study of Africa's security elites - Damman, Erin; Day, Christopher (Conflict, security & development, 2024)
While it has been largely omitted from the broader literature of research ethics, the study of Africa's state militaries presents a set of marked challenges. This article highlights the tensions that emerge in the field between ethics, security management, and methodology in studying Africa's security elites. It engages dominant assumptions that the risks associated with 'the field' come from working in active conflict zones and that protecting research subjects refers to violence-affected civilian populations. Studying the 'legitimate' wielders of violence in Africa takes place in, more often than not, a political context where the field of subjects is restricted to a relatively small group of elites. In such environments, researchers must contend with different modes of positionality and reflexivity where status asymmetries and strict chains of command make it difficult to mediate power dynamics, as security elites tend to be robust gatekeepers of information that follow official narratives. This article is based upon a survey of secondary literature on research ethics and interviews with scholars of African militaries that augment the fieldwork experiences of the authors.